2006
DOI: 10.1007/s10637-006-6335-5
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of 9-nitrocamptothecin and its 9-aminocamptothecin metabolite in relation to ABC transporter genotypes

Abstract: These findings suggest that inter-individual variability in 9AC disposition, but not 9NC, may be influenced, in part, by ABCG2 genotype. In contrast, there was no evidence for a relationship between ABCG2 and the disposition of 9NC, or for relationships between ABCB1 and ABCC2 genotypes and the disposition of 9NC or 9AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 30 publications
(66 reference statements)
1
22
0
Order By: Relevance
“…After intravenous administration, patients who were heterozygous for the 421A allele showed higher levels of plasma diflomotecan than those with wild-type sequences. Other studies reported that the heterozygous 421C>A was associated with increased oral bioavailability of topotecan and the lactone form of 9-aminocamptothecin [81,101]. These results suggest that carriers of the ABCG2 421C>A may have decreased clearance and/or increased oral bioavailability of ABCG2 substrate drugs.…”
Section: Abcg2 (Abcp Bcrp Mxr)mentioning
confidence: 71%
See 1 more Smart Citation
“…After intravenous administration, patients who were heterozygous for the 421A allele showed higher levels of plasma diflomotecan than those with wild-type sequences. Other studies reported that the heterozygous 421C>A was associated with increased oral bioavailability of topotecan and the lactone form of 9-aminocamptothecin [81,101]. These results suggest that carriers of the ABCG2 421C>A may have decreased clearance and/or increased oral bioavailability of ABCG2 substrate drugs.…”
Section: Abcg2 (Abcp Bcrp Mxr)mentioning
confidence: 71%
“…Innocenti et al identified 3972C>T as a SNP potentially affecting ABCC2 activity on irinotecan clearance, where the AUC of irinotecan and metabolites was higher in patients carrying two 3972T alleles [80]. However, a study on the disposition of 9-nitrocamptothecin and its metabolite in relation to ABCC2 polymorphism 3972C>T did not show a significant association [81]. Therefore, up to now the majority of genetic variants of ABCC2 which are not linked to DJS do not demonstrate a major importance for cancer therapy [82].…”
Section: Abcc2 (Cmoat Mrp2)mentioning
confidence: 99%
“…Expression of the Q141K SNP in cell lines has been shown to lead to significantly lower IC50 values for ABCG2 substrates, including mitoxantrone, irinotecan, and SN-38 [119,122]. The Q141K SNP has been shown to influence the pharmacokinetics of orally administered drugs, including topotecan [125], diflomotecan [126] and 9-aminocamptothecin [127]. As noted earlier, the higher plasma drug levels due to the Q141K SNP may result in exquisite sensitivity to certain orally administered chemotherapy drugs.…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…However, de Jong et al reported that ABCG2 C421A genotype did not alter the disposition of irinotecan in European Caucasians [60] . In another study reported by Zamboni et al , ABCG2 genotype partly influenced the inter-individual variability of 9-aminocamptothecin when studied in relation to ABCG2 C421A genotype [61] . Gardner et al reported increased drug accumulation of imatinib, a tyrosine kinase enzyme inhibitor, in cell lines transfected with ABCG2 C421A [62] .…”
Section: Pharmacogenomics Of Abcg2/bcrpmentioning
confidence: 85%
“…Higher plasma levels Difl omotecan Patients Sparreboom 2004 [59] No change Irinotican Patients de Jong 2004 [60] Increased bioavailabilty 9-Aminocamptothecin Patients Zamboni 2006 [61] Increased accumulation Imatinib Transfected cell lines Gardner 2006 [62] Increased accumulation Topotecan Transfected cell lines Imai 2002 [142] No difference Imatinib Patients Gardner 2006 [62] Higher plasma levels Rosuvastatin Healthy volunteers Zhang 2006 [63] No change Pitavastatin Healthy volunteers Ieiri 2007 [64] Expert Opin. Drug Metab.…”
Section: C421a (Exon 5 Q141k)mentioning
confidence: 99%